Dietary Pattern and Nutritional Status of School-going Adolescents in Rural Areas of Bangladesh. - ISLAM, MD. SHAHINUL; ROY, CHANDON; ISHADI, KIFAYAT SADMAN; UDDIN MITHU, MOHAMMAD MEJBAH; ABEDIN, EBNEY SUNJIDA; KARIM, MOHAMMAD SHAHINUR; ALAM, MD. FARHAD; APOU, ARIF CHOWDHURY; CHOWDHURY, ABM ALAUDDIN; MUBARAK, MAHFUZA (Current Research in Nutrition & Food Science, 2024)
Adolescence is a critical phase marked by rapid physical, cognitive, and psychosocial development. This study investigated the dietary patterns and health status of school-going adolescents in rural areas of randomly selected areas of Bangladesh. A cross-sectional study involving 378 participants. Data on socio-demographics, meal consumption patterns, food item frequencies, stunting, and BMI distribution were collected and analysed using descriptive statistics and chi-square tests. Socio-demographic analysis revealed diversity with variations in gender, age, parent's income, and occupation. Food consumption patterns indicated a preference for traditional three meals a day (64.3%). Moreover, daily dietary practice showed that 23.0%, 19.6%, and 6.0% of adolescents in rural areas do not intake fruit, chicken/fish, and vegetables, respectively, at least once a day, while 26% of participants consume fast food regularly. Therefore, BMI analysis showed 37.3% were overweight. Stunting prevalence was 36.0%, with 2.9% severely stunted. Significant associations were found between stunting severity and BMI categories (p < 0.001), gender (p = 0.003), and parents' monthly income (p < 0.001). Gender showed a strong association with BMI categories (p < 0.001), indicating nutritional variations, while age did not exhibit a significant association with BMI of adolescent. In conclusion, the study highlighted complex associations between stunting severity, BMI categories, class levels, and gender among rural adolescents in Bangladesh. Interventions to promote regular balanced diet consumption among schoolgoing children are very important to address nutritional disparities and promote holistic adolescent health in the rural areas of Bangladesh.